Kaidah Amr-Nahy, Qarinah, dan Penafsiran Quraish Shihab tentang Jilbab (Sebuah Kajian Terhadap Kaidah Tafsir) - Aulanni’am, Aulanni’am; Andi Tri Saputra (Aqwal: Journal of Qur'an and Hadis Studies, 2021)
This article tries to discuss and explain how the rules of Amr and Nahy and the concept of Qarinah work in understanding the Qur'an, specifically to obtain a law. This is motivated by the basic rules of Amr and Nahy itself, where each principle basically shows an obligation and prohibition on a case, but the law can change with the  discovery of Qarinah. In this article Qarinah is explained as the proposition, where the arguments can be of various kinds, can be found in the text of the verse itself or other texts, or with the concept of ushul fiqh such as Istihsan, Istislah and Istishab. In this article a particular case is raised to see how Amr-Nahy and the Qarinah concept work, the case is about the law wearing the hijab in the interpretation of the Quraish Shihab, where in its interpretation it does not require the use of the hijab. This article shows how this interpretation is based on a particular Qarinah, in this case closely related to the rules of Istihsan and Urf.